(untitled) (Washington D.C., 1989)
Contents: The constitution: An enduring document; Explaining the constitution: The federalist papers; The executive branch: Powers of the presidency; The legislative branch: The reach of congress; The judicial branch: Interpreting the constitution...
Keywords: Hoa Kỳ,United States; Chính trị và pháp quyền,Politics and government